2005
DOI: 10.2172/859997
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Sensors and Controls for Building Applications: Market Assessment and Potential R&D Pathways

Abstract: PREFACEThis document provides background material on a research and development planning effort in the U.S. Department of Energy (DOE), Office of Building Technologies. It is part of a larger set of material to be used in the ongoing planning process and does not, in itself, represent the decisions or policies of DOE. This document does not represent the current DOE research agenda, nor planned research, but instead is intended to provide a point of departure for discussion of potential research options. v EXE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Sand (2004) reports from a literature review savings of $0.05/sf to more than $1/sf from use of DCV. Brambley et al (2005) report on a market assessment for DCV in 2005; the energy impacts found for DCV are summarized in Table 1.…”
Section: Savings From DCVmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand (2004) reports from a literature review savings of $0.05/sf to more than $1/sf from use of DCV. Brambley et al (2005) report on a market assessment for DCV in 2005; the energy impacts found for DCV are summarized in Table 1.…”
Section: Savings From DCVmentioning
confidence: 99%
“…The need for frequent recalibration (e.g., annually) and the high cost of installation for each zone (or room) makes CO 2 -based control of ventilation at terminal boxes impractical. A multi-lab report (Brambley et al 2005) for the U.S. Department of Energy (DOE) on advanced sensors and controls identifies a need for "development of sensors to determine occupancy number and population distribution within buildings." There are no such terminal unit controllers on the market today to modulate air flow to zones based on actual occupancy.…”
mentioning
confidence: 99%
“…Modern buildings typically use a supervisory computer based Building Management System (BMS) system that coordinates its sensing and control infrastructure, primarily for managing the HVAC system [5]. Most commercial BMSes already provide fault detection features [7], but use simple detection techniques such as threshold monitoring of individual sensors.…”
Section: Introductionmentioning
confidence: 99%
“…BMS systems are thus a critical component for managing energy demand. Improperly configured BMS systems are believed to account for 20% of building energy usage [3], [4]. The general objective of a modern BMS system is to fulfill the occupants' requirements for comfort while reducing energy consumption during building operations.…”
Section: Introductionmentioning
confidence: 99%